Effects of hurdle technology on Monascus ruber growth in green table olives: a response surface methodology approach - Cappato, Leandro P. (Braz J Microbiol, 2017)
An ascomycetes fungus was isolated from brine storage of green olives of the Arauco cultivar imported from Argentina and identified as Monascus ruber. The combined effects of different concentrations of sodium chloride (3.5–5.5%), sodium benzoate (0–0.1%), potassium sorbate (0–0.05%) and temperature (30–40 °C) were investigated on the growth of M. ruber in the brine of stored table olives using a response surface methodology. A full 2(4) factorial design with three central points was first used in order to screen for the important factors (significant and marginally significant factors) and then a Face-Centered Central Composite Design was applied. Both preservatives prevented fungal spoilage, but potassium sorbate was the most efficient to control the fungi growth. The combined use of these preservatives did not show a synergistic effect. The results showed that the use of these salts may not be sufficient to prevent fungal spoilage and the greatest fungal growth was recorded at 30 °C.